2023
DOI: 10.1007/s00414-023-02960-z
|View full text |Cite
|
Sign up to set email alerts
|

A systematic overview of dental methods for age assessment in living individuals: from traditional to artificial intelligence-based approaches

Abstract: Dental radiographies have been used for many decades for estimating the chronological age, with a view to forensic identification, migration flow control, or assessment of dental development, among others. This study aims to analyse the current application of chronological age estimation methods from dental X-ray images in the last 6 years, involving a search for works in the Scopus and PubMed databases. Exclusion criteria were applied to discard off-topic studies and experiments which are not compliant with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 198 publications
0
7
0
Order By: Relevance
“…To the present, the most recent study on the interface between artificial intelligence and dental age estimation was a systematic review 42 . The study has revealed that methods performed “manually” (operator only) tend to generate more marked overestimations (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…To the present, the most recent study on the interface between artificial intelligence and dental age estimation was a systematic review 42 . The study has revealed that methods performed “manually” (operator only) tend to generate more marked overestimations (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…To the present, the most recent study on the interface between arti cial intelligence and dental age estimation was a systematic review 42 . The study has revealed that methods performed "manually" (operator only) tend to generate more marked overestimations (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Modern dental age estimation may achieve better accuracy using statistical tools such as regression and Bayesian calibration or even using artificial-intelligence-based approaches [31]. These methods require strict evaluations of their accuracy, especially for children and young adults aged around 18 years old, if their goal is to help evaluate an individual's minority according to the United Nations Convention on the Rights of the Child.…”
Section: Discussionmentioning
confidence: 99%